A Security Transmission and Early Warning Mechanism for Intelligent Sensing Information in Internet of Things. (25th January 2022) - Qi, Li; Wang, Zetian; Zhang, Di; Li, Yunfa
Abstract : As the demand for intelligent services in the Internet of Things continues to increase, the amount of intelligent sensing information is also increasing, and the security of these information has gradually attracted attention. Owing to the openness and the dynamics of intelligent sensor devices, there are a lot of security issues which needed to be resolved for the corresponding intelligent sensing information. In order to protect the transmission security of intelligent sensing information, this paper proposes a security transmission and early warning mechanism for intelligent sensing information in the Internet of Things. In the security transmission and early waring mechanism, we first propose an encryption/decryption algorithm for intelligent sensing information. Then, we build a security transmission algorithm. On that basis, we propose an early warning algorithm of intelligent sensing information. At the end of this paper, we analyze the security of this mechanism and the results of the experiment in order to illustrate its effectiveness. The results show that our proposed security transmission and early warning mechanism are very effective in the Internet of Things.